Environmental risks from pesticide use: the case of commercial banana farming in northern Lao PDR - Wentworth, A.; Pavelic, Paul; Kongmany, S.; Sotoukee, T.; Sengphaxaiyalath, K.; Phomkeona, K.; Deevanhxay, P.; Chounlamany, V.; Manivong, V. (International Water Management Institute, 2021)
Commercial farming of banana for export has rapidly expanded across northern uplands of Laos since 2008 with the establishment of new plantations by foreign companies. Heavy reliance on agrochemical usage warrants examination of possible environmental and human health risks. This study presents a preliminary assessment of the environmental risks from pesticide usage associated with bananas and other major crops in Oudomxay province. Surface water, groundwater, soil and sediment samples collected from the study area were analyzed for pesticide residues in the laboratory during the wet and dry seasons. Results of the analysis revealed that samples from banana farms had higher concentrations of residues from currently used (CU) pesticides compared with samples from adjacent farms producing maize, rubber, upland rice and gourd. Residues from highly persistent organochlorine (OC) pesticides, such as dichlorodiphenyltrichloroethane, heptachlor, dieldrin and lindane, which are no longer used in Laos, were also detected. Laboratory results were compared against a low-cost pesticide residue detection method and a simple pesticide risk assessment tool. However, neither approach was comparable to laboratory analysis. The potential environmental risk from pesticides and pesticide breakdown products was found to be substantial. For example, concentrations of some CU compounds exceeded the limits set by the World Health Organization. The report highlights several mitigation measures to reduce the environmental risks from hazardous pesticides: (i) increase efforts to eliminate the import and use of hazardous and persistent pesticides; (ii) promote targeted education programs to implement best practices, including the selection and use of pesticides as per international standards, and Integrated Pest Management techniques; (iii) identify and protect drinking water sources with a high risk of contamination; and (iv) maintain vegetated buffers and sediment traps to detain farm runoff, which will allow CU pesticides to degrade to safe levels before entering watercourses.